Scanning electron microscopy of Au585Ag90Cu264Zn61 gold alloy for jewel production - Radiša Perić; Zoran Karastojković; Zorica Kovačević; Dragan Gusković (Zaštita Materijala)
Gold alloys '585' that are used for production of jewelry can be three-, four-, five- and more component alloys. All these alloys are with Au-Ag-Cu base, with constant amount of gold, according to applicable legislation, of 58.5 mass.% Au, while the other components depend on other needs: hardness, plasticity, color, special effects, etc. The investigation was conducted with alloys of yellow color (Au-Ag- Cu-Zn) and of white color (Au-Ag-Cu-Zn-Pd), according to needs and demands of market environment, where the investigation took place, and that is in The Republic of Serbia. With age-hardening in alloys of noble metals, especially in alloys of noble metals with components that crystallize with f.c.c. lattice in certain conditions of previous treatment, as well as temperature and period of ageing, a thermodynamic stabile state of alloy appears, and also a phenomena of hardness and strength of product. The examination of structure of the product, as well as of changes inside the structure of material itself is performed by different mechanic and metallographic methods. One of better methods of overview of changes inside the material structure is examination by scanning electronic microscope - SEM. Beside the structure of material, chemical analysis obtained using the device - detector for energy dispersive spectroscopy - EDS, by which distribution and disposition of elements in one chrismal grain can be determined.